Marginalisasi Perempuan pada Tokoh Utama Novel Mudzakarat Thabibah dan Novel Cinta Suci Zahrana - Selviana, Ika (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2023)
Marginalization still often haunts figures called 'women'. This is because stereotypes are still attached which originate from prejudice and discrimination. This stereotype is what causes the emergence of many forms of marginalization and injustice towards women. The novel Mudzakarat Thabibah by Nawwal Assa'dawi and the novel Cinta Suci Zahrana by Habiburrahman El-shirazy have similar stories regarding the marginalization of women. The two novels will be analyzed using comparative literary studies theory with a liberal feminist theory approach. This research uses a type of library research. The method used by researchers is the qualitative descriptive method. The focus of this research is the form of marginalization of women, the causes of marginalization, and the struggle to face marginalization in female characters. The research results state that there are forms of marginalization of women in the form of control over women's movements, control over creative power, and control over women's reproduction and sexuality. It was also found that the causes of marginalization were stereotypes about women such as having to marry and have children, having to be able to cook, having to be a housewife, and having limited experience.